Adult‐onset cystic fibrosis liver disease: Diagnosis and characterization of an underappreciated entity. Issue 2 (26th June 2017) - Koh, Christopher; Sakiani, Sasan; Surana, Pallavi; Zhao, Xiongce; Eccleston, Jason; Kleiner, David E.; Herion, David; Liang, T. Jake; Hoofnagle, Jay H.; Chernick, Milica; Heller, Theo
Abstract : Cystic fibrosis (CF) liver disease (CFLD), a leading cause of death in CF, is mostly described in pediatric populations. Adult‐onset CFLD lacks sufficient characterization and diagnostic tools. A cohort of CF patients without CFLD during childhood were followed for up to 38 years with serologic testing, imaging, and noninvasive fibrosis markers. Historical CFLD diagnostic criteria were compared with newly proposed CFLD criteria. Thirty‐six CF patients were followed for a median of 24.5 years (interquartile range 15.6‐32.9). By the last follow‐up, 11 (31%) had died. With conventional criteria, 8 (22%) patients had CFLD; and by the new criteria, 17 (47%) had CFLD at a median age of 36.6 years (interquartile range 26.5‐43.2). By the new criteria, those with CFLD had higher median alanine aminotransferase (42 versus 27, P = 0.005), aspartate aminotransferase (AST; 26 versus 21, P = 0.01), direct bilirubin (0.13 versus 0.1, P = 0.01), prothrombin time (14.4 versus 12.4, P = 0.002), and AST‐to‐platelet ratio index (0.31 versus 0.23, P = 0.003) over the last 2 years of follow‐up. Subjects with a FibroScan >6.8 kPa had higher alanine aminotransferase (42 versus 28U/L, P = 0.02), AST (35 versus 25U/L, P = 0.02), AST‐to‐platelet ratio index (0.77 versus 0.25, P = 0.0004), and Fibrosis‐4 index (2.14 versus 0.74, P = 0.0003) and lower platelet counts (205 versus 293, P = 0.02). One CFLD patient had nodular regenerative hyperplasia. Longitudinally, mean platelet counts significantly declined in the CFLD group (from 310 to 230 U/L, P = 0.0005). Deceased CFLD patients had lower platelet counts than those alive with CFLD (143 versus 258 U/L, P = 0.004) or those deceased with no CFLD (143 versus 327U/L, P = 0.006). Conclusion : Adult‐onset CFLD may be more prevalent than previously described, which suggests a later wave of CFLD that impacts morbidity; routine liver tests, radiologic imaging, noninvasive fibrosis markers, and FibroScan can be used algorithmically to identify adult CFLD; and further evaluation in other CF cohorts should be performed for validation. (Hepatology 2017;66:591–601).